2023
DOI: 10.21514/1998-426x-2022-15-4-15-33
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of parental preconceptional irradiation: Endocrine-metabolic pathology in offspring

Abstract: Epidemiological studies of late effects of preconceptional (prior to conception) radiation exposure are necessary in order to understand the risks of tumor and non-tumor pathology in next generations. Research of possible relation between parental preconceptional exposure and development of endocrine and metabolic disorders in the offspring is one of the topical issues of radiation hygiene. The objective of the study: comparative analysis of endocrine and metabolic pathology in children of the individuals expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This suggests that methylation patterns in humans are maintained even through the “epigenetic reset” of spermatogenesis, therefore suggesting a mechanism for epigenetic inheritance via the male gamete in a human family [ 93 ]. Another interesting and recent paper describes the intergenerational effects of exposure to radiation in a Russian cohort [ 94 ]. This retrospective (historical) study based on the Ozyorsk Children’s Health Registry associated the prevalence of endocrine and metabolic pathology in children born and living in Ozyorsk between 1949 and 1973, and preconcepcional exposure of their parents to gamma radiation at the Mayak Production Association, the first atomic industry facility in Russia.…”
Section: Exposure Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that methylation patterns in humans are maintained even through the “epigenetic reset” of spermatogenesis, therefore suggesting a mechanism for epigenetic inheritance via the male gamete in a human family [ 93 ]. Another interesting and recent paper describes the intergenerational effects of exposure to radiation in a Russian cohort [ 94 ]. This retrospective (historical) study based on the Ozyorsk Children’s Health Registry associated the prevalence of endocrine and metabolic pathology in children born and living in Ozyorsk between 1949 and 1973, and preconcepcional exposure of their parents to gamma radiation at the Mayak Production Association, the first atomic industry facility in Russia.…”
Section: Exposure Characteristicsmentioning
confidence: 99%
“…This retrospective (historical) study based on the Ozyorsk Children’s Health Registry associated the prevalence of endocrine and metabolic pathology in children born and living in Ozyorsk between 1949 and 1973, and preconcepcional exposure of their parents to gamma radiation at the Mayak Production Association, the first atomic industry facility in Russia. The researchers found that children of parents working at this nuclear industry had higher prevalence of thyroid diseases, including cancer, comparing to the offspring of low exposed parents—inhabitants of Ozyorsk but not working at the Mayak Production Association [ 94 ].…”
Section: Exposure Characteristicsmentioning
confidence: 99%